The assessment and management of older cancer patients: A SIOG surgical task force survey on surgeons' attitudes. Issue 2 (February 2016) - Ghignone, F.; van Leeuwen, B.L.; Montroni, I.; Huisman, M.G.; Somasundar, P.; Cheung, K.L.; Audisio, R.A.; Ugolini, G.; ,
Abstract: Aim: The Surgical Task Force at SIOG (International Society of Geriatric Oncology) designed this survey to explore the surgical oncologists' approach toward elderly cancer patients. Methods: A web-based survey was sent to all members of ESSO (European Society of Surgical Oncology) and SSO (Society of Surgical Oncology). Results: Two hundred and fifty-one surgeons responded (11% response rate) with a main interest on breast (62.1%), colorectal (43%) and hepatobiliary (27.4%) surgery. Almost all surgeons (>90%) offer surgery regardless the patient's age; only 48% consider mandatory a preoperative frailty assessment. The American Society of Anesthesiologists (ASA) score, nutritional and performance status are most frequently used as screening tools; only 6.4% surgeons use Comprehensive Geriatric Assessment (CGA) in daily practice and collaboration with geriatricians is low (36.3%). If proven to be effective, the majority of surgeons (71%) is prepared to pre-habilitate patients for up to 4 weeks before surgery. One in two surgeons would not offer an operation to patients with impaired cognitive status; conversely, one in three would proceed to surgery regardless of the patient's cognitive status, if functional capacity is conserved. Quality of life and functional recovery are regarded as the most important endpoints in onco-geriatric surgery. Large "real life" prospective observational studies and randomized controlled trials are demanded. Conclusion: Age is not perceived as a limitation to surgery. Screening for frailty is limited. A thorough CGA is seldom used and collaboration with geriatricians is rather uncommon. There is a need for clinical investigations focusing on pre-habilitation and other strategies to achieve better functional recovery.